Organizational justice perception as predictor of job satisfaction and organization commitment - Zuryatie Samidi, 19688-, author; Choi, Sang Long, 1970-, supervisor; Fakulti Pengurusan (2015)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2015